The Role of Parents in Children's Development in The Digital Era - Rubiatin, R; Maksum, Muh. Nur Rochim; Hafidz, H (Universitas Muhammadiyah Surakarta, 2023)
As time goes by, it cannot be denied that the development of information and communication technology is taking place very quickly and rapidly, where the use of technology is now very easily accessible to various groups of society, regardless of age. Nowadays, everyone from toddlers to parents can take advantage of technology, whether in the form of cellphones, computers or other digital media. For children, digital media can be used to stimulate their development, but the use of digital media does not necessarily have positive impacts but also negative impacts, so here the role of parents is needed to monitor children's development, especially in using digital media. Parents should actively involve themselves in their children's digital lives, supervise their use of technology, and guide them to use media ethically, especially for young children who really need extra assistance from their parents.